Chemical variability and optical resolution of linalool in the essential oil of Aeollanthus suaveolens (Lamiaceae) - Siani, A. C. (2013)
The essential oil of Aeollanthus suaveolens (0.07-0.29% yield) was shown to maintain the same chromatographic profile in four consecutive week extractions, during the flowering period, and in eight consecutive week extractions during the non-flowering period. Linalool, -farnesene, and massoilactone were the predominant constituents of the oil, when analyzed by Gas Chromatography coupled to Mass Spectrometry. The oil yield range was lower for the flowering plants. The composition of the oils did not vary qualitatively, linalool being the predominant compound. However, during the flowering period, the linalool content decreased, and -farnesene took its place as the principal signal in the chromatograms. GC chiral analysis showed the presence of a mixture of (l)- and (d)-linalool [(R)- and (S)-linalool respectively] in a proportion varying around 4:1 to 3:1 for all the samples; the higher values being reached during the flowering period, or close to that time. Vacuum distillation of the oil produced a lighter fraction containing up to 76 % of linalool. Other trace compounds were also characterized in the oil, as linalyl acetate, a-terpinenyl acetate, geranyl acetate, a-santalene and cis-a-bergamoptene. and more economical protocol did not affect ex.